SOCIAL CIRCUMSTANCES AND PSYCHOLOGICAL ANLYSIS IN FLAUBERT’S MADAME BOUVARY - Baharuddin, Andi Farid (JURNAL ILMU BUDAYA, 2020)
This research aims to elaborate the The social circumstances and psychological analysis which are existing in Madame Bouvary.  Therefore, the researcher will analyze how social circumstance influences the psychological condition of Emma as the main character of this work. In order to analyze this research, the researcher utilizes the literary psychology approach  as the main theory. Besides, to strengthen the psychological analysis in this work, the researcher uses Abbraham Mashlow theory as the additional perspective. Furthermore, the researcher uses qualitative methodology both for collecting data and analyzing data. In collecting the primary data, the researcher gathers the information through the work and for collecting the supporting data, the researcher collects it from books which related to this research. The results research shows that the social circumstance in the novel has been influencing Emma’s characteristics in some particular aspects such as (1) psychological needs, (2) savety needs, (3) the love and belonging needs, (4) self estem, and (5) self actualization.